Computer simulation and modelling of electrical characteristics of ferroelectric films for device applications - Lee, Teng Mong. (2008)
Ferroelectric thin film materials have attractive properties such as high dielectric constant and reversible, large remnant polarisation. These properties have made these materials attractive in applications, namely in the areas of non-volatile random access memory (NV-RAM) and ultra-high density dynamic random access memory (DRAM).